The cyclicality of sales, regular and effective prices: Business cycle and policy implications - Olivier Coibion; Yuriy Gorodnichenko; Gee Hee Hong (Bank of Canada, 2013)
We study the cyclical properties of sales, regular price changes and average prices paid by consumers (effective prices) using data on prices and quantities sold for numerous retailers across many U.S. metropolitan areas. Inflation in the effective prices paid by consumers declines significantly with higher unemployment while little change occurs in the inflation rate of prices posted by retailers. This difference reflects the reallocation of household expenditures across retailers, a feature of the data which we document and quantify, rather than sales. We propose a simple model with household store-switching and assess its implications for business cycles and policymakers.
Keywords: E3; E4; E5; 330; Inflation and prices; Transmission of monetary policy; Monetary policy framework